2021
DOI: 10.3390/children8121134
|View full text |Cite
|
Sign up to set email alerts
|

School Performance among Children and Adolescents during COVID-19 Pandemic: A Systematic Review

Abstract: As a result of COVID-19 restrictions, conventional ways of schooling were not possible, and in order to continue the educational process new digital resources, such as online learning platforms, were imposed. Although virtual courses provided high-quality educational material, the efficiency in children’s and adolescents’ academic performance in general is yet to be known. The purpose of this systematic review is to examine whether the academic performance of school-aged students was impacted or not through on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
54
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(76 citation statements)
references
References 52 publications
3
54
0
4
Order By: Relevance
“…Regarding the quantitative results, recent studies have also documented the academic problems that has been caused by the COVID-19 restrictions in classrooms [61,62]. Studies around the world refer to a decrease in students' mathematics achievement due to the pandemic with similar decreases in students' achievement to those reported in this research [63][64][65][66]. In this sense, many researchers in the field state that the in-person support prior to COVID-19 without restrictions produced higher achievement results than the online solutions or in-person adaptations that are currently taking place [67,68].…”
Section: Discussionsupporting
confidence: 66%
“…Regarding the quantitative results, recent studies have also documented the academic problems that has been caused by the COVID-19 restrictions in classrooms [61,62]. Studies around the world refer to a decrease in students' mathematics achievement due to the pandemic with similar decreases in students' achievement to those reported in this research [63][64][65][66]. In this sense, many researchers in the field state that the in-person support prior to COVID-19 without restrictions produced higher achievement results than the online solutions or in-person adaptations that are currently taking place [67,68].…”
Section: Discussionsupporting
confidence: 66%
“…Other research on adolescents’ academic achievement or motivation during distance education during a pandemic is ambiguous. The systematic review by Panagouli et al [ 46 ] revealed that students either suffered from learning losses compared to pre-pandemic years or, in some cases, they benefited from online learning. The review showed that most of the students presented a significant decrease in mathematics scores compared to previous years.…”
Section: Discussionmentioning
confidence: 99%
“…The review showed that most of the students presented a significant decrease in mathematics scores compared to previous years. Younger students faced more difficulties during online learning; however, they presented more enthusiasm for learning materials because they were more creative and interactive [ 46 ]. In our interviews, the adolescents did not report specific subjects that would have suffered more due to distance learning than others.…”
Section: Discussionmentioning
confidence: 99%
“…On average, students spent less time learning and reported more distractions (Huber & Helm, 2020). The corresponding learning loss during the first pandemic wave has been summarized by several systematic reviews and meta-analyses (De Witte & Smet, 2021;Donnelly & Patrinos, 2021;Hammerstein et al, 2021;Panagouli et al, 2021;Zierer, 2021). Standardized learning losses were typically smaller in native language domains such as reading than in mathematics (e.g., Zierer, 2021, reported d2020-pre= -0.10 in reading compared to d2020pre = -0.17 in mathematics).…”
Section: Introductionmentioning
confidence: 99%